Meningkatkan Kemampuan Berbicara Melalui Model SIUUL Pada Anak TK Kelompok B TK Nurul Falah Jakarta - Ruhaeti , Rita; Watini , Sri; Widiyastuti , Arie (CV. ITTC INDONESIA, 2024)
This research aims to improve the speaking abilities of kindergarten Group B children at TK.Nurul Falah Kp.Dukuh, Kelurahan Kebayoran Lama Selatan, Kecamatan Kebayoran Lama, Kota Jakarta Selatan, by using the SIUUL Model (listen, speak, repeat). The speaking abilities include fluency, sentence structure, vocabulary and articulation. The research method used is Classroom Action Research (CAR), conducted collaboratively with teachers and utilizing the Kemmis and Taggart model, consisting of two cycles. Each cycle includes planning, implementation, observation, and reflection. The subjects of the research are 10 children from Group B at TK Nurul Falah Jakarta. The object of the research is the improvement of speaking abilities through the SIUUL Model. Data collection was carried out through observations using observation sheets. Data analysis was conducted descriptively and quantitatively. The success indicator for speaking ability is 75%. The reaseach results indicate that the implementation of the SIUUL Model can improve children’s speaking abilities after the intervention. Pre-Intervention results show that 60% of the children were in the “Not yet Develop’ category, 30% were “Begining to Develop”, 10% were “Developing as Expected”, and none were in the “Very Well Developed” category.After the first cycle of intervention, there was an improvement : 20% were “Not Yet Developed:, 50% were “Begining to Develop” 30% were “Developing as Expected”. Since the first cycle did not meet the expected indicators, a second cycle was conducted, resulting in no children in the “Not Yet Develop’ category, 10% “Beginning to Develop”, 10% “Develop as Expected”, and 80% in the “Very Well Developed” category. Thefore, in the implementation of the SIUUL Model can improve the speaking abilities of Group B kindergarten children at TK Nurul Falah Jakarta.